An outbreak of hemolytic uremic syndrome in southern Romania during 2015-2016: Epidemiologic, clinical, laboratory, microbiologic, therapeutic and outcome characteristics - Mihaela Balgradean; Anca Croitoru; Eugene Leibovitz (Elsevier, 2019)
Background and aims: To describe the epidemiologic, clinical, microbiological, therapeutic and outcome characteristics of a HUS outbreak occurring in southern Romania from 2015 to 2016. Methods: We retrospectively collected data from the medical records of all HUS cases hospitalized at the pediatric nephrology department of Marie Curie Children's Hospital of Bucharest, Romania. Results: There were 32 HUS cases (19 girls/13 boys, 87.6% <2 years), all associated with diarrhea (bloody in 13, 40.6%). Thirteen (40.6%) and 4 (12.5%) patients had oliguria and anuria at admission. Extreme pallor, generalized edema, vomiting, dehydration, fever and seizures were found in 100%, 56.3%, 31.3%, 31.3%, 25% and 9.4% of patients, respectively. E. coli and STEC were identified in the stools of 6 and 8 patients, respectively; E. coli O26 and O157 infection were documented serologically in 10 and 3 children, respectively. There were 15/32 (46.9%) patients with confirmed HUS. Eighteen (56.3%) patients were hypertensive; other complications included infections, left ventricular hypertrophy, cardiopulmonary arrest, seizures and encephalopathy in 62.5%, 37.5%, 28.3%, 18.8% and 12.5%, respectively. Peritoneal dialysis and hemodialysis were performed in 23 (72%) and 2 patients, respectively. Three patients (9.4%) died early during hospitalization. A 6-12-month follow-up of 26 patients revealed that 65.4% had post-HUS sequelae (persistent hypertension and chronic renal failure in 34.6% and 30.8%, respectively). Conclusions: The principal STEC serotype involved was O26:H11 and the number of confirmed HUS cases reached half of the patients. Compared with the medical literature, this outbreak had a higher rate of complications and renal sequelae and was associated with a high fatality rate. Key Words: children, dialysis, Escherichia coli O26, hemolytic uremic syndrome, hypertension